Powers of the Secular Modern - Isa Blumi (International Institute of Islamic Thought, 2007)
For more than three decades, anthropologist Talal Asad has challenged the governing assumptions of western “knowledge” of the non-western world. In fact, his itinerate career marks the parameters of a dynamic and crucial period in western academia. It is Asad’s undermining of British social anthropology in the late 1960s and ethnographic functionalism in general that anticipates the postcolonial theories that would emerge many years later. More than being a simple icon of a generation that challenged the conventions of Orientalism, it is Asad’s essential (if often unacknowledged) contribution to our current self-critical engagement with the larger world that makes this book so valuable.